DEVELOPMENT OF STABLE NANOSUSPENSION LOADED ORAL FILMS OF GLIMEPIRIDE WITH IMPROVED BIOAVAILABILITY - Kilor, Vaishali; Sapkal, Nidhi; Daud, Anwar; Humne, Shruti; Gupta, Tushar (International Journal of Applied Pharmaceutics, 2017)
Objective: In the present work attempt has been made to stabilize optimized nanosuspensions of glimepiride by solidification using a novel Oral Thin Film (OTF) formulation. Methods: Nanosuspensions were characterized for particle size, zeta potential as well as in vitro dissolution profile. As nanosuspensions are prone to destabilization by Ostwald's ripening or agglomeration/aggregation, OTF formulation as a novel approach for stabilization through solidification of optimized nanosuspension was attempted. OTF formulation method is a simple, easy and scalable method for the preparation of solid oral dosage form. Prepared formulations were evaluated for physicochemical parameters like folding endurance, disintegration time, tensile strength, in vitro drug release, in vivo bioavailability and stability. Results: The mean particle size of the nanoparticles in OTF was found to be 57.2 nm. It was observed from the results of in vivo bioavailability studies that high plasma drug concentrations(Cmax) were achieved for nanosuspension loaded OTF (NSOTF) i.e. 4900 ng/ml as compared to marketed oral formulation (Cmax-2900 ng/ml). Results of the stability studies indicated that nanosize of the particles was retained even after 3 mo of the study. Conclusion: Therefore it can be concluded that OTF formulation has a potential for stabilization of nanosuspensions.